The Impact of Dry Eye Disease on Health-Related Quality of Life Among Elderly Chinese Population in Taiwan: Insights From the Shihpai Eye Study - Su-Ying Tsai; Tung-Mei Kuang (Vision Science and Eye Health Journal, 2025)
Introduction: Advanced age is a significant risk factor for dry eye disease. Many individuals tend to perceive dry eye as a minor and inconsequential problem. The significant adverse impact of dry eye on an individual’s health perception cannot be underestimated. This issue demands substantial attention in public health, particularly considering the growing aging population. The present study aimed to investigate the association between dry eye symptoms and signs with health-related quality of life in an Asian elderly population. Purpose: The present study aimed to investigate the association between dry eye symptoms and dry eye signs on health-related quality of life in an Asian elderly population. Methods: This cross-sectional study was conducted within the Shihpai community in Taipei, Taiwan, involving individuals aged 65 years and older who lived independently in the community. A baseline examination was conducted in 1999, consisting of a structured questionnaire that included dry eye symptoms and the 36-item short form health survey (SF-36) questionnaire, followed by a standardized ophthalmic examination that included slit lamp and dry eye tests. Results: Frequent symptoms of dry eye are related to all domains of SF-36 except role limitation due to emotional problems. Schirmer test (≤ 5 mm) was found to have a significant association with greater bodily pain (p = 0.0307) when accounting for other covariates. Additionally, meibomian gland disease exhibited a significant link to lower scores in the domain of role limitation due to emotional problems (p = 0.0406). Conclusions: Our study demonstrated that dry eye, particularly its symptoms, has a significant negative impact on the health-related quality of life in the elderly. It was reported that effective intervention of dry eye could alleviate symptoms of anxiety and depression. Further study will be required to assess whether treatment of dry eye would also improve the health-related quality of life in elderly participants.